2013
DOI: 10.1371/journal.pone.0070146
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of AtSHN1/WIN1 Provokes Unique Defense Responses

Abstract: The plant cell cuticle serves as the first barrier protecting plants from mechanical injury and invading pathogens. The cuticle can be breached by cutinase-producing pathogens and the degradation products may activate pathogenesis signals in the invading pathogens. Cuticle degradation products may also trigger the plant’s defense responses. Botrytis cinerea is an important plant pathogen, capable of attacking and causing disease in a wide range of plant species. Arabidopsis thaliana shn1-1D is a gain-of-functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 65 publications
0
29
0
Order By: Relevance
“…This protein is annotated as a basic peroxidase (theoretical pI 8.85) and has been described as one of the closest homolog to ZePrx (Herrero et al ). This protein is expressed in healthy, non‐stressed plants, but its expression is also induced under fungi, bacteria and insect attack (Little et al , Mohr and Cahill , Floerl et al , Sela et al ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This protein is annotated as a basic peroxidase (theoretical pI 8.85) and has been described as one of the closest homolog to ZePrx (Herrero et al ). This protein is expressed in healthy, non‐stressed plants, but its expression is also induced under fungi, bacteria and insect attack (Little et al , Mohr and Cahill , Floerl et al , Sela et al ).…”
Section: Resultsmentioning
confidence: 99%
“…AtPrx52 has been reported to be expressed in roots (Méndez‐Bravo et al ), shoots (Méndez‐Bravo et al ), leaves (Little et al , Floerl et al , Sela et al ) and stamen (Cai and Lashbrook ). However, despite its close homology to ZePrx, which is highly expressed in hypocotyls and epicotyls, no bibliographic data are available concerning the expression of AtPrx52 in Arabidopsis stems.…”
Section: Resultsmentioning
confidence: 99%
“…It was previously reported that overexpression of the TF WIN1 increases cuticle thickness (Broun et al, 2004;Kannangara et al, 2007) and results in susceptibility to B. cinerea (Sela et al, 2013), which contrasts with the phenotypes of the cdk8 mutant. These observations suggest that CDK8 and WIN1 have overlapping functions.…”
Section: Cdk8 and Med25 Interact With The Ethylene Response Tf Win1mentioning
confidence: 95%
“…LACS2 encodes a member of the long-chain acyl-CoA synthases involved in cutin biosynthesis in Arabidopsis (Schnurr et al, 2004). Interestingly, WIN1 overexpression results in increased expression of several wax biosynthesis genes, increased alkane levels, and susceptibility to fungal infection (Broun et al, 2004;Sela et al, 2013). Due to the lack of appropriate loss-of-function alleles of the WIN1 gene, we could not make direct comparisons of the win1 and cdk8 mutants.…”
Section: The Differential Impact Of Cdk8 On Responses To Necrotrophicmentioning
confidence: 99%
“…Plant cuticle is also vital for plant growth and development; it prevents or promotes postgenital organ fusion and mediates interactions between pollens and pistils (Lolle, Hsu, & Pruitt, 1998). Previous studies have shown that disruption of cuticle formation or patterning in plants affects not only vegetative and reproductive development but also responses to biotic or abiotic stresses (Aharoni et al, 2004;Kurdyukov et al, 2006;Lolle et al, 1998;Panikashvili et al, 2007Panikashvili et al, , 2010Sela et al, 2013;Shi et al, 2011Shi et al, , 2013Sieber et al, 2000;Smirnova et al, 2013). Among them, defective-cuticle-induced postgenital fusion between vegetative and reproductive organs or between floral organs often results in defective growth and development and abnormal stress response.…”
Section: Hsp70-16 Is Involved In Sepal Cuticle Formation and Pattermentioning
confidence: 99%